Sarcopenia and Frailty in Elderly Trauma Patients - Fairchild, Berry (World J Surg, 2015)
BACKGROUND: Sarcopenia describes a loss of muscle mass and resultant decrease in strength, mobility and function that can be quantified by CT. We hypothesized that sarcopenia and related frailty characteristics are related to discharge disposition after blunt traumatic injury in the elderly. METHODS: We reviewed charts of 252 elderly blunt trauma patients who underwent abdominal CT prior to hospital admission. Data for thirteen frailty characteristics were abstracted. Sarcopenia was measured by obtaining skeletal muscle cross sectional area (CSA) from each patient’s psoas major muscle using Slice-O-Matic® software. Dispositions were grouped as dependent and independent based on discharge location. Chi-square, Fisher’s exact, and logistic regression were used to determine factors associated with discharge dependence. RESULTS: Mean age 76 years, 49% male, median ISS 9.0 (IQR=8.0–17.0). Discharge destination was independent in 61.5%, dependent in 29% and 9.5% of patients died. Each 1 cm(2) increase in psoas muscle CSA was associated with a 20% decrease in dependent living (p<0.0001). Gender, weakness, hospital complication, and cognitive impairment were also associated with disposition; ISS was not (p=0.4754). CONCLUSIONS: Lower psoas major muscle CSA is related to discharge destination in elderly trauma patients and can be obtained from the admission CT. Lower psoas muscle CSA is related to loss of independence upon discharge in the elderly. The early availability of this variable during the hospitalization of elderly trauma patients may aid in discharge planning and the transition to dependent living.